Smart Contact-Less Attendance System - Akhilesh Nawale, Naman Agrawal, Piyush Parakh, Sheetal Sobale, Dnyaneshwari Navale, Samruddhi Pate (Mathematical Statistician and Engineering Applications, 2022)
The advancement of technology, as well as the influence of contactless systems in our lives has been noticed across time. It has a very large impact on a variety of fields. Almost every work today is performed by a computer. Obtaining information and promptly converting it into a product that consumers desire is very relieving work and all of this is done nowadays. Since the Covid-19 outbreak , we are moving towards contactless instruments. Infrared thermometers have been used to examine individuals at airports, train stations, and other crowded places. These scans are being used to find potential Covid-19 or any other viral infectious patients. In this project, a smart contactless attendance system is made which can be used by employees of a firm or students in an institute for passing through a temperature test and without touching, register their attendance which further will be stored in a database.